LEGAL PROTECTION OF CHILDREN AS VICTIMS OF CRIME ACTIONS AND SEXUAL VIOLENCE - Ikama Dewi Setia Triana; Eti Mul Erowati (Program Studi Ilmu Hukum, Jurusan Hukum dan Kewarganegaraan, Fakultas Hukum dan Ilmu Sosial, Universitas Pendidikan Ganesha, 2024)
This article aims to analyze legal protection for children as victims of moral crimes. This research uses a normative juridical research method with a type of approach, namely a statutory approach and a conceptual approach. The legal materials used are primary, secondary and tertiary legal materials, obtained by conducting literature studies. The research results show that the implementation of protection for children who are victims of violence is still not optimal. This is because victims' rights, such as the right to receive rehabilitation, compensation and restitution, make it difficult to manage the release of funds, because there is confusion from law enforcement officials regarding where the funds should be used from. A very fundamental obstacle to implementing the protection of children as witnesses and victims is that there are no funds provided to maximize the implementation of this protection. And in general, protection for child victims of immoral crimes can be carried out in 3 (three) ways, namely: (1) Punishing perpetrators of immoral crimes against children with heavy criminal sanctions so that the objectives of the punishment can be achieved based on the provisions of the Law (2) By provide compensation to child victims of immoral crimes by providing restitution charged to the perpetrator of the immoral crime. (3) By carrying out rehabilitation for child victims of immoral crimes.